Exploring opportunities for tuning phenyltris(pyrazol-1-yl)borate donation by varying the extent of phenyl substituent fluorination. Issue 17 (4th April 2023) - Fischer, Paul J.; Roe, Charley B.; Stephenson, Jasmine N.; Dunscomb, Rachel J.; Carthy, Camille L.; Nataro, Chip; Young, Victor G.
Abstract : Complexes of 3, 4, 5-trifluorophenyl- and 3, 5-bis(trifluoromethyl)phenyltris(pyrazol-1-yl)borates have been prepared for comparison to pentafluorophenyl analogues to assess if donor modulation at κ 3 - N, N, N bound metals is feasible via this strategy. Abstract : The importance of electron deficient Tp ligands motivates the introduction of electron-withdrawing substituents into the scorpionate framework. Since perfluorophenyltris(pyrazol-1-yl)borate affects significant anodic shifts in half-cell potentials in their metal complexes relative those of phenyltris(pyrazol-1-yl)borate analogues, the tuning opportunities achieved using 3, 4, 5-trifluorophenyl- and 3, 5-bis(trifluoromethyl)phenyl(pyrazol-1-yl)borates were explored. Bis(amino)boranes ((3, 4, 5-F)C6 H2 )B(NMe2 )2 and ((3, 5-CF3 )C6 H3 )B(NMe2 )2 are precursors to fluorinated tris(pyrazol-1-yl)phenylborates. Thallium salts of these scorpionates exhibit bridging asymmetric κ 3 - N, N, N coordination modes consistent with the reduced π-basicity of the fluorinated phenyl substituents relative those of other structurally characterized tris(pyrazol-1-yl)phenylborates. While a comparative analysis of the spectral and X-ray crystallographic data for classical Mo(0), Mo(ii ), Mn(i ), Fe(ii ) and Cu(ii ) complexes of [((3, 4, 5-F)C6 H2 )Bpz3 ] − and [((3, 5-CF3 )C6 H3 )Bpz3 ] − could not differentiate these ligands with respect to their metal-based electronic impacts, cyclic voltammetry suggests that 3, 4, 5-trifluorophenyl- and 3, 5-bis(trifluoromethyl)phenyl(pyrazol-1-yl)borates affect similar anodic shifts within their metal complexes, with coordination of [((3, 5-CF3 )C6 H3 )Bpz3 ] − rendering metal centers more difficult to oxidize, and sometimes even more difficult to oxidize than their [C6 F5 Bpz3 ] − analogues. These data suggest that the extent of phenyl substituent fluorination necessary to minimize metal center electron-richness in phenyltris(pyrazol-1-yl)borate complexes cannot be confidently predicted.